2017
DOI: 10.1155/2017/1247138
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Ocular Symptoms and Signs in Patients with Dry Eye

Abstract: Purpose. To analyze the correlations between the ocular surface signs and symptoms in patients with dry eye. Methods. In this observational study, 176 dry eye patients, including 60 males and 116 females, were enrolled and their dry eye symptoms and ocular signs were observed. Partial correlation analysis was conducted between OSDI score and each ocular surface sign, and the correlations were further discussed in different age groups. Then multiple linear regression analysis was used to further explore the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…This result was already shown in many studies and confirmed the weak correlation between signs and symptoms in DED. 31 33 Interestingly, in our study, the OSI was correlated with OSDI score and particularly with the ocular symptoms subscale (sensitivity to light, grittiness, pain, blurred vision, and poor vision). This result suggested that tear film instability induced aberrations and scattering, and consequently fluctuating vision that is perceived by patients.…”
Section: Discussionsupporting
confidence: 48%
“…This result was already shown in many studies and confirmed the weak correlation between signs and symptoms in DED. 31 33 Interestingly, in our study, the OSI was correlated with OSDI score and particularly with the ocular symptoms subscale (sensitivity to light, grittiness, pain, blurred vision, and poor vision). This result suggested that tear film instability induced aberrations and scattering, and consequently fluctuating vision that is perceived by patients.…”
Section: Discussionsupporting
confidence: 48%
“…DED can be assessed based on a combination of symptoms and signs. However, several studies reported poor correlation between DED symptoms and signs [26][27][28]. Dryness symptoms could be assessed systematically using validated questionnaires that include questions allow for the monitoring of dryness symptoms and their frequency and or their severity over time [29].…”
Section: Introductionmentioning
confidence: 99%
“…The procedures currently used to detect and diagnose DED can be unreliable and often do not reveal the form of DED which is occurring in the patient. As an example, the Schrimer test depend on capillary migration of tears into a filter paper, and the migration distance is used to determine the absence or presence of DED [1819]. A short migration distance may indicate the cause is aqueous-deficient DED (ADDED), but inserting the paper strips can influence the results.…”
Section: Introductionmentioning
confidence: 99%